2019
DOI: 10.3389/fped.2019.00301
|View full text |Cite
|
Sign up to set email alerts
|

Transition for Adolescents and Young Adults With Asthma

Abstract: Asthma is a complex, heterogenous medical condition which is very common in children and adults. The transition process from pediatric to adult health care services can be a challenge for young people with chronic medical conditions. The significant changes in physical and mental health during this time, as well as the many unique developmental and psychosocial challenges that occur during adolescence can complicate and impede transition if not adequately addressed and managed. The transition period can also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 88 publications
4
42
0
Order By: Relevance
“…15 However, young people's voices are not usually included in health-care transition research to the extent needed 54 and their experiences of transitions in care outside specialist services across the health-care system remains largely unexamined. Top-down approaches to health-care service planning 55 that do not involve patients dominate current provision. 56 Self-management of SCD is demanding and requires close self-monitoring [e.g.…”
Section: Chapter 1 Contextmentioning
confidence: 99%
“…15 However, young people's voices are not usually included in health-care transition research to the extent needed 54 and their experiences of transitions in care outside specialist services across the health-care system remains largely unexamined. Top-down approaches to health-care service planning 55 that do not involve patients dominate current provision. 56 Self-management of SCD is demanding and requires close self-monitoring [e.g.…”
Section: Chapter 1 Contextmentioning
confidence: 99%
“…16 Studies have reported the importance of having good communication skills and having good knowledge of medication intake before being considered as ready to be moved over to adult care. 16,17 We noted that excellent communication skills alongside good knowledge of ones chronic illness did not translate to acceptability of change from paediatric care to adult-oriented care, because although females had better communication skills and were more open to ask questions, the knowledge acquired from the interaction did not positively affect their readiness to move over to adult care. This emphasizes the need to start on time to impart communication and interaction skills to children as this will be of great benefit to them even during the pre-transition stage.…”
Section: Discussionmentioning
confidence: 95%
“…Based on their respective population in the clinics, we recruited consecutively the proportionate sample size required from the various clinics: 63, 39, 36 and 23 from, HIV, sickle cell anaemia, asthma, nephrology clinics, respectively. To collect data on transition readiness, the validated intervieweradministered Self-management and Transition to Adulthood with Treatment (STARx) questionnaire [15][16][17] was pretested and found to have good internal consistency (Cronbach's alpha 0.8), and was used via intervieweradministered survey. The STARx questionnaire also has external validity meaning that it can be applied to make deductions outside the context of children with asthma, sickle cell, nephrotic syndrome and HIV disease as it has been applied across a wide range of several other chronic conditions and found to be a sound tool that informed decisions for those chronic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found the negative experience with healthcare provider influenced health-seeking behaviour 46 . Children should be reviewed for asthma even if the asthma is mild, as it could recur in adulthood, and childhood asthma is a risk factor for later developing pulmonary disease 47 . The National Asthma and Education Program suggested that parents should inform the teacher about their children's written asthma action plan to guide the teacher during emergencies rather than waiting for parents to fetch their children at school without taking immediate action that could save a life.…”
Section: Discussionmentioning
confidence: 99%